Enhanced deep-blue emission from Pt(II) complexes bound to 2-pyridyltetrazolate and an ortho-xylene-linked bis(NHC)cyclophane - McGee, Karen; Wright, Phillip; Muzzioli, S.; Siedlovskas, C.; Raiteri, Paolo; Baker, M.; Brown, David; Stagni, S.; Massi, Massimiliano (The Royal Society of Chemistry, 2013)
The coordination of 2-pyridyltetrazolate and ortho-xylene-linked bis(NHC)cyclophane to Pt(II) yielded a novel complex characterised by enhanced pure deep-blue emission, whose intensity can be modulated via methylation of the tetrazole ring.